산림조사 자료의 표본점 할당 모델링을 통한 고해상도 산림공간정보 구축 - 김승욱; Seunguk Kim; 하의린; Uirin Ha; 이성재; Sung-jae Lee; 임종수; Jongsu Yim; 한희; Hee Han; 최혜영; Hyeyeong Choe (한국산림과학회지, 2025)
기후위기 속에서 산림의 가치는 더욱 중요해지고 있으며, 이를 극대화하기 위해서는 수종 구성, 영급 분포, 구조적 특성, 탄소저장량 등 종합적인 산림공간정보가 필수적이다. 최근 머신러닝 기반 공간분석을 응용하여 표본점 중심의 산림조사 자료를 넓은 지역으로 확장하는 연구가 활발하며, 이를 국내 산림 환경에 적용하기 위한 검토가 필요하다. 이 연구는 지리산 지역을 대상으로 랜덤 포레스트(random forests) 기반의 표본점 할당 모델링을 수행하여 임목 수준의 고해상도 산림공간정보를 구축하였다. 이를 위해, 국립공원연구원, 서울대학교 남부학술림의 산림조사 자료를 일관된 기준으로 통합하였으며, 세 자료를 선택하는 조합에 따라 총 7개의 모형을 구성하여 성능을 다각적으로 검증한 후 최적의 모형을 선정하였다. 표본점 할당 모델링은 연구지역 각 지점에서 임상, 임분고, 경급이 가장 유사한 표본점을 식별하여 산림조사 자료를 할당하도록 설계하였다. 모형 학습에서는 산림조사 지점에서 분류된 임상, 임분고, 경급의 식생변수를 다중반응변수로 설정하였고, 각 지점의 환경변수를 결합하여 참조자료로 이용하였다. 학습된 모형은 임상도, 기후, 지형, 위치 등의 환경정보를 포함하는 목표자료에 따라 연구지역 전반에 표본점을 할당하였으며, 최종적으로 100 m × 100 m 해상도의 래스터(raster) 기반 공간자료를 생성하였다. 모형 성능 평가 결과, 단일 기관의 자료만으로 구성한 모형은 해당 기관의 조사 특성이 과도하게 반영되어 특정 산림 유형을 과대 혹은 과소 추정하는 경향을 나타냈다. 그에 반해, 세 기관의 자료를 모두 통합하여 활용한 모형은 산림조사 자료 및 임상도를 재현하는 성능이 가장 우수하였으며, 전체적인 산림 분포 패턴을 안정적으로 예측하였다. 이 연구의 표본점 할당 모델링은 표본점의 고유번호를 가지는 래스터 지도를 제공하여, 사용자가 고유번호와 연결된 상세 산림정보에 접근하고 다양한 속성지도를 제작할 수 있도록 한다. 따라서 이 프레임워크는 수종의 분포 예측, 산림 구조 분석, 탄소저장량 평가 등 다양한 분야에 적용될 수 있으며, 산림조사 자료의 활용성을 크게 향상할 수 있다. 다만, 모형의 특성상 넓은 지역을 대상으로 할 때는 산림조사 지점과의 국지적 일치율이 낮아질 수 가능성이 있으며, 좁은 지역에서는 균형 잡힌산림조사 자료를 이용해 희소한 생태계의 정보를 충분히 확보해야 한다. 향후 산림조사 자료의 활용도를 더욱 높이려면 기관 간 조사 프로토콜을 표준화하고, 모델링 과정에서 각 기관 조사방식의 차이를 면밀히 분석하여 반영할 필요가 있다. Forests are increasingly valuable as climate change intensifies, and their conservation management requires comprehensive spatial information on the species composition, stand age distribution, structural characteristics, and carbon storage. Recent studies have employed machine learning-based spatial analyses for plot-based forest surveys across broad regions, but the effectiveness of this approach in South Korea remains understudied. We applied a plot imputation approach using random forests to create a high-resolution tree-level forest map of the Jiri Mountain. We standardized and integrated forest survey data from the Korea Forest Service, Korea National Park Research Institute, and Seoul National University Nambu Forest and then built seven models for evaluation. Each model identified sample points with similar vegetation attributes (class, height, and diameter) across the study area. We trained the models using a reference dataset of vegetation and environmental variables and then assigned sample points throughout the study area based on target datasets including a forest-type map and environmental data on climate, topography, and location to generate a raster map at a 100 m × 100 m resolution. When applied to a single-institution dataset, the models tended to over- or under-estimate certain vegetation attributes likely due to survey biases. Integrating all three datasets resulted in a more balanced view of overall forest patterns and yielded the highest reproduction accuracy. The developed framework generates raster maps with unique plot identifiers to enable users to access plot details and create thematic maps for the species distribution, forest structure, and carbon storage. However, uneven distribution of the survey points may cause local losses of accuracy. Balanced forest surveys are crucial for capturing details about rare or specialized ecosystems. Standardizing survey protocols across institutions and carefully examining the differences in each dataset will be crucial to enhancing both the data quality and modeling applications of the framework.